Effect of Chicken Bile Application on Scar Healing Process - limanda, Claudia Felicia; Intizam, Marwa Humaira; Jusuf, Pierre Joshua; Tanujaya, Monica Aprilia; Rusyati, Luh Made Mas (Bali Dermatology Venereology and Aesthetic Journal, 2023)
Type of scars varies from mild fine line scars to abnormal scars which treatment will differ according to its type, site, symptoms, and severity. Scars have a great impact of human life, namely physically, aesthetically, psychologically, and socially that make choosing the right treatment very important. Treatment for scars can be done conventionally in health care facilities and traditionally. Chinese traditional medicine has been known to have a major role in scar treatment. One of the examples is the use of chicken bile. "Chicken bile", "Chicken bile effect", "Wounds", and "Wound healing process" were the keywords applied to scientific online databases. Wound healing is composed of three initial stages, such as inflammatory, proliferative, and remodeling stage. Chicken bile is known to have a low but strong bilirubin level with little biliverdin. These agents can serve as antipyretic, antioxidant, anti-inflammatory, and anti-atherogenic that can aide wound healing. Bile also supports protein metabolism, fat metabolism, energy production, and synthesis of glycogen. Most importantly, bile contains matrix metalloproteinases (MMPs) that function to degrade type IV collagen which have an important role in wound reepithelization process, altering wound matrix, enabling cell to migrate, and tissue remodeling. Thus, it is certain that MMPs are essential in wound healing.